A systematic review of tranexamic acid usage in patients undergoing femoral fracture surgery - Zhang P (Dove Medical Press, 2018)
Pei Zhang,1,* Jianzhong Bai,1,* Jinshan He,2 Yuan Liang,2 Pengtao Chen,2 Jingcheng Wang1,2 1Dalian Medical University, Dalian, Liaoning, People’s Republic of China; 2Department of Orthopedics, Clinical Medical College of Yangzhou University, Subei People’s Hospital of Jiangsu Province, Yangzhou, People’s Republic of China *These authors contributed equally to this work Background: Patients undergoing femoral fracture surgery frequently require blood transfusion. Tranexamic acid (TXA) has been widely used to decrease transfusion rate in joint replacement surgery. Therefore, we conducted a systematic review to evaluate the efficacy and safety of TXA usage in femoral fracture surgery.Materials and methods: Studies involving TXA usage in femoral fracture surgery were searched through four electronic databases. The end points included total blood loss, postoperative hemoglobin decline, transfusion rate, thromboembolic events, 90-day mortality, and operative time. The present study was performed following Cochrane Reviewers’ Handbook and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and was carried out by using Stata 14.0 software.Results: Eleven studies concerning intravenous (IV) application of TXA and three studies concerning topical administration of TXA were included. Twelve studies were randomized controlled trials (RCTs), and one was a retrospective cohort study. Regarding IV TXA, our paper indicated that the IV TXA group had less total blood loss (weighted mean difference [WMD] = -319.282, P = 0.000), lower postoperative hemoglobin decline (WMD = -1.14, P = 0.000) and lower transfusion rate (risk difference [RD] = -0.172, P = 0.000). No significant differences were found in thromboembolic events (RD = 0.008, P = 0.507), 90-day mortality (RD = 0.009, P = 0.732) and operative time (WMD = -2.227, P = 0.103). Regarding topical TXA, no significant differences were found in the transfusion rate (RD = -0.098, P = 0.129), postoperative hemoglobin decline (WMD = -1.137, P = 0.231), thromboembolic events (RD = -0.017, P = 0.660) and operative time (WMD = -4.842, P = 0.136).Conclusion: Our meta-analysis demonstrated that both IV and topical application of TXA reduced transfusion rate in femoral fracture surgery. However, still further studies are needed to identify the optimal route of administration, TXA dosage and timing. In addition, high-quality RCTs with a large sample size are required to figure out the safety of TXA application, especially in the elderly, before its wide recommendation. Keywords: femoral fracture, tranexamic acid, systematic review